Gut commensals and their metabolites in health and disease - Krishnamurthy, Hari Krishnan; Pereira, Michelle; Bosco, Jophi; George, Jaimee; Jayaraman, Vasanth; Krishna, Karthik; Wang, Tianhao; Bei, Kang; Rajasekaran, John J. (Frontiers in Microbiology, 2023)
Purpose of review: This review comprehensively discusses the role of the gut microbiome and its metabolites in health and disease and sheds light on the importance of a holistic approach in assessing the gut. Recent findings: The gut microbiome consisting of the bacteriome, mycobiome, archaeome, and virome has a profound effect on human health. Gut dysbiosis which is characterized by perturbations in the microbial population not only results in gastrointestinal (GI) symptoms or conditions but can also give rise to extra-GI manifestations. Gut microorganisms also produce metabolites (short-chain fatty acids, trimethylamine, hydrogen sulfide, methane, and so on) that are important for several interkingdom microbial interactions and functions. They also participate in various host metabolic processes. An alteration in the microbial species can affect their respective metabolite concentrations which can have serious health implications. Effective assessment of the gut microbiome and its metabolites is crucial as it can provide insights into one’s overall health. Summary: Emerging evidence highlights the role of the gut microbiome and its metabolites in health and disease. As it is implicated in GI as well as extra-GI symptoms, the gut microbiome plays a crucial role in the overall well-being of the host. Effective assessment of the gut microbiome may provide insights into one’s health status leading to more holistic care.